SUBTITLING FILM UN MONSTRE À PARIS KARYA BIBO BERGERON - Annisa, Firda Nur; Hasyim, Muhammad; Bandu, Iriyanti (Universitas Hasanuddin, 2019)
This study aims to analyze the shift in form and meaning of the translated text in the film (subtitle) Un Mostre À Paris by Bibo Bergeron from French to Indonesian. This research used a qualitative descriptive method by applying the Catford form shift theory and the Simatupang meaning shift theory. The subjects in this study were all words, phrases, clauses and sentences. While the object in this study is the text translation in the film (subtitle) Un Mostre À Paris by Bibo Bergeron released in 2011. The results show that there are shape-shifts in the form of 2 level shifts, four structural shifts, 8-word category shifts, 8 unit shifts and four intra-system shifts. The shapeshift occurs because of differences in the structure of the two languages. There is also a shift in meaning in the form of 4 shifts in meaning because of the cultural point of view.